Pendampingan Pengembangan Pemasaran Desa Wisata Kreatif Sumber Sirah Di Desa Kerkep Kecamatan Gurah Kabupaten Kediri - Berlian Fahruddin; Widyatmoko Widyatmoko (Lembaga Pengembangan Kinerja Dosen, 2024)
Currently, many tourist villages are emerging which are included in edutourism with a variety of tourism potential within them. It is known as an edutourism-based Creative Tourism Village because most of the tourist attraction concepts in Kerkep fall into the creative category and can add to the education of tourists, especially the tourist attraction icon of the Kerkep Creative Tourism Village, namely the Sumber Sirah water tourism. The purpose of this service is because this village is a village that has great potential in developing edutourism. For this reason, a marketing process is needed to carry out promotions that have not been fully used by partners because of the technological tools that need to be understood. This community service activity uses a presentation method, implementation method with direct visits, and discussion forums through assistance regarding digital marketing via social media. Implementation of service consists of planning, implementation and evaluation stages. The results of the service presented material by the service team about what marketing is. After the material has been presented, the participants can try to practice it accompanied by the staff. The implementation of the service carried out at the partner's location went well because the participants easily understood the marketing material without significant obstacles, thus this learning method can be utilized and can be used as an alternative to other marketing methods